Thin Film Silicon Nanowire/PEDOT:PSS Hybrid Solar Cells with Surface Treatment - Wang, Hao (2017)
SiNW/PEDOT:PSS hybrid solar cells are fabricated on 10.6-μm-thick crystalline Si thin films. Cells with Si nanowires (SiNWs) of different lengths fabricated using the metal-catalyzed electroless etching (MCEE) technique have been investigated. A surface treatment process using oxygen plasma has been applied to improve the surface quality of the SiNWs, and the optimized cell with 0.7-μm-long SiNWs achieved a power conversion efficiency (PCE) of 7.83 %. The surface treatment process is found to remove surface defects and passivate the SiNWs and substantially improve the average open circuit voltage from 0.461 to 0.562 V for the optimized cell. The light harvesting capability of the SiNWs has also been investigated theoretically using optical simulation. It is found that the inherent randomness of the MCEE SiNWs, in terms of their diameter and spacing, accounts for the excellent light harvesting capability. In comparison, periodic SiNWs of comparable dimensions have been shown to exhibit much poorer trapping and absorption of light.